Policy advisory committees in Kenya: interest group participation and effectiveness - David Irwin; Mercy Kyande (International Review of Public Policy)
Governments create advisory committees and arm’s-length agencies and then delegate responsibilities and powers, sometimes merely to provide policy advice but sometimes to implement regulation. Interest groups, and especially groups representing private businesses, are often appointed to such committees. As a result, they proactively seek appointment to policy advisory committees and boards established by government, believing that this offers one route amongst several to promote their interests to government and to influence public policy. But little is known about whether they are then successful in influencing policy outcomes. This paper addresses that gap – specifically by reviewing interest groups’ perceptions of their effectiveness, given the challenges of assessing actual effectiveness, in policy advisory committees in Kenya. Whilst it is possible that the policy outcomes simply reflect the policy preferences of the interest groups, these groups believe that they exert some influence on the committees on which they sit – through the provision of research evidence, clearly articulated opinion, and reasoned argument – and they further believe that the committees exert some influence on government policy.